Structural modification of luteolin from Flos Chrysanthemi leads to increased tumor cell growth inhibitory activity. Issue 15 (1st August 2016) - Yang, Chao; Chen, Hui; Lu, Shihai; Zhang, Meng; Tian, Wei; Wang, Mingping; Zhang, Ling; Song, Yunlong; Shen, Aijun; Zhou, Youjun; Zhu, Ju; Zheng, Canhui
Graphical abstract: Abstract: The luteolin from Flos Chrysanthemi was found to directly bind to the Bcl-2 protein and inhibit the tumor cell growth in our previous study. However, it has been shown to possess wide and week biological activities. In this study, a series of derivatives of luteolin were designed and synthesized, and their tumor cell growth inhibitory activities were evaluated against human leukemia cell line HL-60. The results showed that compounds1B-2, 2A-3, and2B-5, with hydrophobic substituted benzyl groups introduced to B ring and hydrogen or methyl introduced to 7-OH group of luteolin, exhibited the strongest inhibitory activity with the IC50 lower than 10 μM, which were significantly more potent than luteolin. The studies presented here offer a good example for modifications of flavones to improve their tumor cell growth inhibitory activities.